Inclusion of thin target and source regions in alimentary and respiratory tract systems of mesh-type ICRP adult reference phantoms. (17th February 2017) - Kim, Han Sung; Yeom, Yeon Soo; Nguyen, Thang Tat; Choi, Chansoo; Han, Min Cheol; Lee, Jai Ki; Kim, Chan Hyeong; Zankl, Maria; Petoussi-Henss, Nina; Bolch, Wesley E; Lee, Choonsik; Qiu, Rui; et al.
Abstract: It is not feasible to define very small or complex organs and tissues in the current voxel-type adult reference computational phantoms of the International Commission on Radiological Protection (ICRP), which limit dose coefficients for weakly penetrating radiations. To address the problem, the ICRP is converting the voxel-type reference phantoms into mesh-type phantoms. In the present study, as a part of the conversion project, the micrometer-thick target and source regions in the alimentary and respiratory tract systems as described in ICRP Publications 100 and 66 were included in the mesh-type ICRP reference adult male and female phantoms. In addition, realistic lung airway models were simulated to represent the bronchial (BB) and bronchiolar (bb) regions. The electron specific absorbed fraction (SAF) values for the alimentary and respiratory tract systems were then calculated and compared with the values calculated with the stylized models of ICRP Publications 100 and 66 . The comparisons show generally good agreement for the oral cavity, oesophagus, and BB, whereas for the stomach, small intestine, large intestine, extrathoracic region, and bb, there are some differences (e.g. up to ~9 times in the large intestine). The difference is mainly due to anatomical difference in these organs between the realistic mesh-type phantoms and the simplified stylized models. The new alimentary and respiratory tract models in the mesh-type ICRP reference phantoms preserve the topology and dimensions of the voxel-type ICRP phantoms and provide more reliable SAF values than the simplified models adopted in previous ICRP Publications .